(untitled) (Archives of Criminology, 1974)
The printed elaborations, in this part of the Archives, contain the re sults of research conducted by the Department of Criminology, Institute of Legal Sciences, Polish Academy of Sciences anfddeal with three categories of people: ‒ 564 offenders were qualified as having committed acts of hooliganism in Warsaw, in 1964, in an inebriate state, acts combined with physical aggression on people unknown to the offender; further delinquency of these offenders is checked during the course of eight years; ‒ approximately 900 who were in 1967 charged with “disturbance of public peace or indecent behaviour in a public place, (Art. 27, decree on fighting alcoholism); out of a random sample of 300 delinquents charged with these offences, information was obtained regarding their further appearances in court (Penal Administrative Commission) for the period of five years (till the end of 1972), arrests by the police while intoxicated and court convictions; ‒ 500 men and 250 women, listed in detoxication centres at least three times (women twice), during the period of over 5 and a half years till the second half of 1970, about whom information was gathered, regarding also other arrests by the police while intoxicated, ending up in the detoxication centre, as well as information about their court convictions; with part of the cases information was obtained about the follow-up period of the investigated during the years 1971-1973. The above-mentioned three categories were taken into account, because research was to embrace only those offenders who while committing the offence were intoxicated. These examinations were to reveal the dimensions of heavy drinking and of their delinquency. Research conducted by the Department of Criminology so far which took into account alcoholism, dealt with people, mainly from among young adult and adult recidivists marked by serious social degradation. Efforts were made to find out whether and since when they were drinking alcohol to excess and to what extent they were alcoholics. Taken into account was the category of recidivists, revealing symptoms of alcoholism. This research concentrated on various individuals where one actually could expect the possibilities of frequent or systematic heavy drinking, but in regard to whom no information was available regarding the frequency of deviations in the behaviour of the investigated under the influence of alcohol, as well as data about their delinquency, neither its intensification nor the type of offences committed. Despite the fact that it was impossible in the studies presented here to conduct individual psychological and medical examinations, or environmental research, nevertheless the collected large amounts of material seem to enable us to get an idea about the phenomenon of a large scope and social significance. Together with the increase in excessive drinking of alcohol in many countries there also emerges the category of people having conflicts with the penal code while intoxicated and of people charged with disturbance of public peace. There are relatively few studies of this large population, committing as a rule minor offences. Initiating such research the Department of Criminology, Institute of Legal Sciences, Polish Academy of Sciences intended above all to find out how often various categories of persons, committing typical offences connected with drunkenness, are “problem drinkers” with intensified symptoms of deviations in behaviour and how many of them have already to be considered alcoholics. Such findings can be most significant when planning campaigns, aimed at revealing at an early stage cases requiring the interference of institutions set up to fight alcoholism, in order to prevent in such a way the spreading of certain offences and crimes.